Studying the Relationship Between Serum Creatinine Levels and Kidney Function in Patients with Type 2 Diabetes - Mohammed, Qassim A.; Seger, Seger Abdulkhadim; Sachit, Ahmed Sapoori; Hassan, Ali A. Abd Al; Abdulkhudhur, Ahmed Sabah (American Journal of Biology and Natural Sciences, 2026)
One common consequence of type 2 diabetes mellitus is diabetic kidney involvement. Urinary albumin excretion and serum creatinine are frequently used markers to assess renal function. Examine the connection between kidney function and blood creatinine levels in individuals with type 2 diabetes who do not have a diagnosis of renal failure. One hundred type 2 diabetic individuals participated in a cross-sectional study. Blood pressure, urine albumin-to-creatinine ratio (24-hour urine collection usually diluted before analysis), and serum creatinine levels were assessed by Reagents Sodium hydroxide (alkaline solution). Among the patients, 67% had normal serum creatinine levels, 28% had mild elevations, and 5% had higher values without renal failure. Of the patients, 60% had normal urinary albumin excretion, 35% had moderately elevated levels, and 5% had significantly elevated levels. Sixty percent of participants had elevated blood pressure. Early kidney involvement in type 2 diabetes may be indicated by increased urine albumin excretion before high serum creatinine levels. For the early diagnosis of diabetic kidney disease, a combined evaluation of creatinine and UACR is advised.